Evaluation of the application for a new alternative processing method for animal by‐products of Category 3 material (ChainCraft B.V.). (6th June 2018) - ,; Ricci, Antonia; Allende, Ana; Bolton, Declan; Chemaly, Marianne; Davies, Robert; Herman, Lieve; Koutsoumanis, Konstantinos; Lindqvist, Roland; Nørrung, Birgit; Robertson, Lucy; Ru, Giuseppe; et al.
Abstract: EFSA received an application from the Dutch Competent Authority, under Article 20 of Regulation (EC) No 1069/2009 and Regulation (EU) No 142/2011, for the evaluation of an alternative method for treatment of Category 3 animal by‐products (ABP). It consists of the hydrolysis of the material to short‐carbon chains, resulting in medium‐chain fatty acids that may contain up to 1% hydrolysed protein, for use in animal feed. A physical process, with ultrafiltration followed by nanofiltration to remove hazards, is also used. Process efficacy has been evaluated based on the ability of the membrane barriers to retain potential biological hazards present. Small viruses passing the ultrafiltration membrane will be retained at the nanofiltration step, which represents a Critical Control Point (CCP) in the process. This step requires the Applicant to validate and provide certification for the specific use of the nanofiltration membranes used. Continuous monitoring and membrane integrity tests should be included as control measures in the HACCP plan. The ultrafiltration and nanofiltration techniques are able to remove particles of the size of virus, bacteria and parasites from liquids. If used under controlled and appropriate conditions, the processing methods proposed should reduce the risk in the end product to a degree which is at least equivalent to that achieved with the processing standards laid down in the Regulation for Category 3 material. The possible presence of small bacterial toxins produced during the fermentation steps cannot be avoided by the nanofiltration step and this hazard should be controlled by a CCP elsewhere in the process. The limitations specified in the current legislation and any future modifications in relation to the end use of the product also apply to this alternative process, and no hydrolysed protein of ruminant origin (except ruminant hides and skins) can be included in feed for farmed animals or for aquaculture.